Effectiveness of an Educational Program on Nurse’s Knowledge Regarding Nursing Management of Thrombolytic Therapy for Patients with Acute Myocardial Infraction at Teaching Hospitals and Cardiac Care Centers in Baghdad City - Hami, Haider B.; Atiyah, Hussein H. (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: This study aims to evaluate the effectiveness of an educational program on cardiac care units nurse’s knowledge regarding nursing management of thrombolytic therapy for patients with acute myocardial infarction at teaching hospitals and cardiac care Centres in Baghdad city. and to find out the relationships between nurse’s knowledge and their socio-demographic characteristics (age, gender, level of education, years of experience in nursing, years of experience in cardiac care units, and participation in training session). Methodology: A quasi- experimental design applied in Ibn Al-nafees teaching hospital and Ibn Al-Bitar center for cardiac surgery from 18th December 2019, to 24th March 2020. A non - probability purposive sample was randomly selected (40) nurses from cardiac care units, the sample divided into two groups (20) nurses considered as study group and another (20) nurses considered as control group. The study group was exposed to an educational program, while the control group was not exposed to the program. Data collection was done at two times: baseline data (before any intervention was provided to the study group) and 21 days after giving the educational program (in the study group). The data was collected, by using of a questionnaire, which consists of two parts, part (1) demographic data form that consists of (8) items, the part (2) that consists of (3) domains (40) items concerning nurses' knowledge. The validity of the questionnaire was determined by presenting it to (23) specialist experts and its reliability was determined through a pilot study. The data analysis through using statistical analysis procedures. Results: the results of this study shows that there is a highly significant differences related to nurses' knowledge regarding nursing management for thrombolytic therapy for acute myocardial infarction patients; between pre and post-test in the study group, however there is a minor differences between pre and post-test in the control group. Conclusion: Nurses' knowledge regarding nursing management for thrombolytic therapy for acute myocardial infarction patients has been improved after application of the educational program in the study group, which confirmed the effectiveness of the provided program to improving nurses knowledge, the study concluded that there is a significant association between nurses knowledge and their socio-demographic characteristics in term of level of education and years of experience in cardiac care units (CCU). Recommendation: The researcher recommended the necessity of continuing applying this program to a broader sample.